Identifying genetic variants that contribute to chemotherapy-induced cytotoxicity. (September 2007) - Hartford, Christine M; Dolan, M Eileen
Patients treated with anticancer chemotherapy exhibit variation, both in terms of tumor response and the incidence and severity of adverse effects. The etiology of this variation is multifactorial with genetic factors likely contributing to a significant extent. Pharmacogenetic and genomic studies can be used to identify the genetic variants that contribute to interindividual variation in susceptibility to chemotherapy-induced cytotoxicity. This review will describe candidate and whole-genome approaches, describe the advantages and disadvantages of each, and illustrate how they can be used to obtain clinically relevant information. Specific emphasis is given to recent advances emerging from the International HapMap Project and to the development of genetic signatures, as opposed to expression signatures, to explain drug sensitivity and resistance.